Periradicular repair after single-visit root canal treatment using sonic irrigant activation of teeth with apical periodontitis - Arıkan, Nur Sena; Erdem Hepşenoğlu, Yelda; Erşahan, Şeyda; Özçelik, Fatih (My University, 2024)
Objectives: This study aimed to explore whether using sonic irrigant activation during endodontic treatment favors periradicular repair in teeth with apical periodontitis. Materials & methods: One clinician treated 140 posterior (either premolar or molar) asymptomatic teeth with periapical lesions: 70 were randomly assigned to the sonic activation with EndoActivator (EA) group, and 70 were treated by conventional needle irrigation (CNI). Both groups underwent chemomechanical root canal preparation using 35/04 diameter rotary files and 2.5% NaOCl as the irrigant. NaOCl was sonically activated in the EA group, and the final irrigation with NaOCl was performed using a 30-gauge side-perforated needle in the CNI group. All root canal obturations were performed with lateral compaction. All patients were followed up for 12 months. Success was determined based on both healed and healing cases. The chi-square or Fisher’s exact test was used to compare success rates and outcome-influencing factors between groups. Results: The recall rate was 131 (94%). At 12 months, 50 teeth (77%) were considered healed, 12 teeth (18%) as healing, and three (5%) as failed in the EA group, while 43 teeth (65%) were considered healed, 17 (26%) as healing, and six (9%) as failed in the CNI group. Verbal Rating Scale scores were significantly lower in the EA group than in the CNI group on postoperative days 1 (p < 0.0001) and 2 (p = 0.0002). Postoperative Periapical Index scores were significantly lower in the EA group than in the CNI group (p = 0.0023). Postoperative lesion sizes were also significantly smaller in the EA group (0.7 [0.2–11.7] mm) than in the CNI group (1.7 [0.5–11.5] mm; p = 0.0118). While the success rate was higher in the EA group (62 [95%]) than in the CNI group (60 [91%]), the difference was not significant (p = 0.492). Conclusions: The periradicular repair of posterior teeth with apical periodontitis demonstrated the efficacy of EndoActivator on treatment outcomes and reduced postoperative pain. These results suggest the adjunctive use of sonic activation to enhance the decontamination of the root canal system during the chemomechanical stage. Clinical relevance: This clinical trial is the first to evaluate the effects of sonic activation on postoperative healing. Sonic activation with the EndoActivator can reduce postoperative pain and accelerate the healing of the periapical tissues.
Keywords: Apical Periodontitis; Endoactivator; Periradicular Repair; Root Canal Therapy; Single-Visit Root Canal Treatment; Sonic Irrigant Activation